Evolutionary theory of ageing and the problem of correlated Gompertz parameters. (7th November 2016) - Burger, Oskar; Missov, Trifon I.
Abstract: The Gompertz mortality model is often used to evaluate evolutionary theories of ageing, such as the Medawar–Williams' hypothesis that high extrinsic mortality leads to faster ageing. However, fits of the Gompertz mortality model to data often find the opposite result that mortality is negatively correlated with the rate of ageing. This negative correlation has been independently discovered in several taxa and is known in actuarial studies of ageing as the Strehler–Mildvan correlation. We examine the role of mortality selection in determining late-life variation in susceptibility to death, which has been suggested to be the cause of this negative correlation. We demonstrate that fixed-frailty models that account for heterogeneity in frailty do not remove the correlation and that the correlation is an inherent statistical property of the Gompertz distribution. Linking actuarial and biological rates of ageing will continue to be a pressing challenge, but the Strehler–Mildvan correlation itself should not be used to diagnose any biological, physiological, or evolutionary process. These findings resolve some key tensions between theory and data that affect evolutionary and biological studies of ageing and mortality. Tests of evolutionary theories of ageing should include direct measures of physiological performance or condition. Highlights: Parameters in the Gompertz mortality model are negatively correlated. This correlation is not due to mortality selection on heterogeneity in frailty. The correlation is a problematic statistical artefact of the Gompertz distribution. The correlation should not be used to diagnose evolutionary or biological processes. Direct physiological measures should be used in tandem with actuarial techniques.